A review of the Silba admirabilis McAlpine species group (Diptera: Lonchaeidae) with descriptions of thirteen new species from the Afrotropical region - Macgowan, Iain (Zootaxa, 2015)
The Silba admirabilis species group is diagnosed within the genus Silba Macquart by the combination of partly yellow tarsomeres and the distinctive features of the male genitalia. Thirteen new species within this species group are described from the Afrotropical region; namely Silba bakongo MacGowan sp. nov., Silba boulangi MacGowan sp. nov., Silba bredoi MacGowan sp. nov., Silba garamba MacGowan sp. nov., Silba hambai MacGowan sp. nov., Silba inimvua MacGowan sp. nov., Silba lubumbashi MacGowan sp. nov., Silba mbuti MacGowan sp. nov., Silba saegeri MacGowan sp. nov., Silba spiculata MacGowan sp. nov., Silba tekei MacGowan sp. nov., Silba upemba MacGowan sp. nov., and Silba wittei MacGowan sp. nov. Ten previously described species within the genus Silba are also identified as belonging to the S. admirabilis species group. One species of the genus Lonchaea also belonging to this group is re-assigned to Silba. The synonymies Silba displata McAlpine, 1964 = Silba hilli (Malloch, 1928) and Silba fragranti MacGowan, 2007 = Silba chalkei McAlpine, 1956 are established. A key and illustrations of male genitalia are provided to all species. Further information is presented relating to the taxonomy and distribution of previously described members of this species group whose range extends from the Afrotropical to Australasian regions.